(3ef QcGFR GdOYhI (B/s - (3GdgdGdj, eLOjs ((3GdbGgQI (B:s (3OGQ GdJhRjY hGdfTQ GdESdGejI,s, 1995)
(3jJfGhd cJGH (B((3QcGFR GdOYhI(B) (3hGdPj bGe HJCdjag O(B. (3eLOj GdgdGdj, aj MhGdj (B(208) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3QcGFR GdOYhI(B) (3GdcJGH jhVM Cfg GLJeYJ Ydi CeJfG cd Cee GdCQV, ef UdjHjjf MGbOjf hTjhYjjf edMOjf, hjghO WGeYjf(B. (3dGHO ef Yed OAhH eJhGUd jhbX GdfGS ef SHGJge hjMQc ajge eYGfj GdLgGO hGdHPd, acGfJ GdOYhI aj gPG GdhbJ aj CeS GdMGLI Edi QLGd ef fhY NGU jMedhfgG hjSjQhf HgG, hdf jJCJi gPG EdG ef NdGd QcGFR eJjfI JUeO aj hLg GdeDGeQGJ hJYdj cdeI Gddg aj GdCQV(B. s
(3HHdjhLQGajI (B: (3UaMI (B199-203.s
Keywords: (3GdOjf GdESdGejs -- (3hYX hEQTGOs